Boula Matari Tintin – młody belgijski reporter jedzie do Konga - Renata Niziołek (Ksiegarnia Akademicka Publishing, 2021)
The author of the article attempts to answer the following question: to what extent in the Polish translation of Hergé’s cartoon Tintin in the Congo is it possible to create a negroidal variant of language which is called „le petit nègre” in the French source text. The essential difference between these texts is related to the fact that the number of similar examples of stylizations in Polish literature is relatively small (compared to French literature).